Peliputan Secara Langsung Persidangan Perkara Pidana Oleh Media Televisi Dihubungkan Dengan Asas Pemeriksaan Di Pengadilan Terbuka Untuk Umum Dalam Rangka Pembaharuan Hukum Acara Pidana - Ardilla, Merti; Rusmiati, Elis; Tajudin, Ijud (UI Scholars Hub, 2020)
In the practice of judiciary in Indonesia, the phenomenon of direct trial of cases of punishment by the press appeared and then broadcast live through television media, this could occur in a situation as a trial announced for the public. This practice has a negative impact, among others, will refute the principle of the presumption of innocence and have an impact on the evidence at the trial. This study aims to find out and analyze the provisions regarding the coverage of trials in court by disputes with the public interest and the principle of examination at the trial open to the public. As well as to find the coverage of the trial in the court by the press in the future during the discussion with the principle of examination at the trial, it was open to the public in the framework of renewal of the prison procedure law.